276 Evaluation of a Long-acting Growth-promoting Implant (Revalor-XS) as an Initial Implant in a Re-implant Program with a revalor-200 Terminal Implant in Feedlot Cattle: A Three-study Pooled Analysis. (7th May 2021) - Crawford, Grant I; Nichols, Wade T; Hutcheson, John P; Streeter, Marshall N; Nuttelman, Brandon L; Walter, Lee-Anne J; Renter, David G; Amrine, David
Abstract: Data from three large-pen feedlot studies were pooled to evaluate use of a long-acting implant (Revalor-XS) as an initial implant in a re-implant program. The three studies consisted of 2, 764 steers in 40 pens, with an initial body weight (BW) of 271 kg. Treatments consisted of Revalor-IS [80 mg trenbolone acetate (TBA), 16 mg estradiol (E2)] administered on arrival, followed by Revalor-200 (200 mg TBA, 20 mg E2) terminal implant (IS/200) or Revalor-XS (80 mg TBA, 16 mg E2 uncoated; 120 mg TBA, 24 mg E2 coated; 200 mg TBA, 40 mg E2 total) on arrival followed by Revalor-200 terminal implant (XS/200). Steers were fed to equal days-on-feed (DOF) within study and averaged 210 DOF. Steers within treatment were re-implanted at same DOF in two studies (Day 124 on average followed by an 81-day terminal implant window). In the third study, IS/200 steers were implanted on Day 120 and XS/200 steers on Day 140 of the 217-day study. Final BW averaged 635.6 and 638.3 kg for IS/200 and XS/200, respectively (P = 0.21). There were no differences (P > 0.26) in DMI, ADG and Gain:Feed between treatments. Hot carcass weight tended (P = 0.07) to be greater with XS/200 (412.7 kg) compared with IS/200 (409.1 kg). Ribeye area was greater (P < 0.01) and fat thickness tended (P = 0.06) to be lower with XS/200 compared with IS/200. Distributions of USDA quality grades were not affected (P = 0.26) by treatment. Distributions of USDA yield grades (YG) were affected (P = 0.01) by treatment with a shift toward more YG 1 and 2 carcasses with XS/200 and more YG 4 and 5 carcasses with IS/200. This analysis indicates that using Revalor-XS as an initial implant leads to greater carcass weight and ribeye area and lower YG when compared with Revalor-IS.